S100A9 as a potential novel target for experimental autoimmune cystitis and interstitial cystitis/bladder pain syndrome - Jiang Zhao; Mi Zhou; Chengfei Yang; Yang-Wuyue Liu; Teng Yang; Bishao Sun; Benyi Li; Ji Zheng; Shuangshuang Dai; Zhenxing Yang; Xiangwei Wang (Biomarker Research)
Abstract Background Interstitial cystitis/bladder pain syndrome (IC/BPS) is a chronic inflammatory disease of the bladder for which no effective therapy is currently available. Understanding the pathogenesis of IC/BPS and identifying effective intervention targets are of great clinical importance for its effective treatment. Our work focuses on elucidating the key targets and underlying mechanisms of IC/BPS. Methods We established an experimental autoimmune cystitis (EAC) mouse model and generated gene knockout mice to elucidate key mediators triggering chronic inflammatory damage in IC/BPS through using single-cell RNA sequencing, proteomic sequencing, and molecular biology experiments. Results Our study revealed that the infiltration and activation of macrophages, T cells, and mast cells exacerbated inflammatory bladder damage in both IC/BPS and EAC mice. Notably, cell-cell communication among bladder immune cells was significantly enhanced in EAC mice. Macrophages, as the main cell types altered in EAC mice, received and transmitted the most intensity signalling. Mechanistically, macrophages synthesized and secreted S100A9, which in turn facilitated macrophage polarization and promoted the production of pro-inflammatory cytokines. S100A9 emerged as an important pro-inflammatory and pathogenic molecule in IC/BPS and EAC. Further analysis demonstrated that S100A9 activation enhanced the inflammatory response and exacerbated bladder tissue damage in IC/BPS patients and EAC mice via TLR4/NF-κB and TLR4/p38 signalling pathways. Importantly, inhibition of S100A9 with paquinimod, as well as genetic knockout of S100A9, significantly attenuated the pathological process. Conclusions S100A9 is an important pro-inflammatory and pathogenic molecule in IC/BPS and EAC. Targeting S100A9-initiated signalling pathways may offer a novel therapeutic strategy for IC/BPS.